Gastronomy and Industrialized Food in the Aymara Communities of the Pilcuyo District, El Collao Province - Ilave -Puno-Peru - Alanoca , Vicente; Apaza, Jorge; Calderon, Alfredo; Ticona, Cesario; Maquera, Yuselino (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The research addresses a topic of social interest that is gastronomy and industrialized foods in the Aymara context, which with its varied forms and styles, differs from other gastronomies. The aim of the research is to present the wisdom of preparing meals and consumption of the population they produce and extent of industrialized foods. For this, the qualitative method and the technique of ethnography have been used. As a result of exploration it is noticed that in the Andes the cuisine of each day is varied (breakfast, lunch and dinner), the preparation of meals of the peasant families are based on what is done by raising agrobiodiversity, on what nature offers such as: plants, wild animals and minerals. On the other hand, industrialized food that is easily obtained in the local market. The consumption is closely related to weather stations of the agricultural year, which are: "jallupacha or ch’uxñapacha " (rainy season) and " awtipacha " (dry season).